2023
DOI: 10.1021/acs.langmuir.3c01285
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Engineering of Porous Pd/M (M = Au, Cu, Mn) Sponge-like Nanocrystals with a Clean Surface for Enhanced Alkaline Electrochemical Oxidation of Ethanol

Adewale K. Ipadeola,
Ahmed Abdelgawad,
Belal Salah
et al.

Abstract: The interfacial engineering of Pd-based alloys (i.e., PdM with distinct morphologies, compositions, and strain defects) is an efficient way for enhanced catalytic activity; however, it remains a grand challenge to fabricate such alloys in aqueous solutions without heating, organic solvents, and multiple reaction steps. Herein, we present a simple, aqueous-phase, one-step, and ultrafast approach for the interfacial engineering of surfactant-free porous PdM (M = Cu, Au, and Mn) nanocrystals with well-controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 62 publications
(163 reference statements)
0
1
0
Order By: Relevance
“…Optimizing the utilization of palladium atoms is at the forefront of current research endeavors . Several methods have been developed to precisely control the morphology, scale, structure, and composition of palladium (Pd)-based nanocatalysts to enhance their catalytic performance. Several studies have shown that adding a second or third metallic element (M 1 and M 2 ) to palladium-based binary (PdM) or ternary (PdM 1 M 2 ) alloys significantly increases the reaction rates of oxygen reduction reactions (ORR) and alcohol oxidation reactions (AOR). , For instance, a series of porous palladium- and platinum-based alloys were synthesized and exhibited exceptional electrocatalytic properties. Highly efficient electrode catalysts with ultra-low Pt loadings were obtained by depositing Pt on three-dimensional hydroxylated Ti 3 C 2 T x MXene nanonet or porous carbon substrates. Alloying processes refine the catalyst’s morphology and electronic configuration, thereby elevating its catalytic efficiency and resistance to poisoning during ethanol oxidation reactions. , The optimized morphology typically contains numerous nanopores and a large specific surface area. Such enhancement can substantially augment ion transport within the nanostructures, thereby offering an abundance of active sites on lattice planes for the catalysis of ethanol oxidation. , Furthermore, the optimized electronic structure enhances KOH/C 2 H 5 OH adsorption and electron transfer during the reaction process, resulting in an improved recovery rate.…”
Section: Introductionmentioning
confidence: 99%
“…Optimizing the utilization of palladium atoms is at the forefront of current research endeavors . Several methods have been developed to precisely control the morphology, scale, structure, and composition of palladium (Pd)-based nanocatalysts to enhance their catalytic performance. Several studies have shown that adding a second or third metallic element (M 1 and M 2 ) to palladium-based binary (PdM) or ternary (PdM 1 M 2 ) alloys significantly increases the reaction rates of oxygen reduction reactions (ORR) and alcohol oxidation reactions (AOR). , For instance, a series of porous palladium- and platinum-based alloys were synthesized and exhibited exceptional electrocatalytic properties. Highly efficient electrode catalysts with ultra-low Pt loadings were obtained by depositing Pt on three-dimensional hydroxylated Ti 3 C 2 T x MXene nanonet or porous carbon substrates. Alloying processes refine the catalyst’s morphology and electronic configuration, thereby elevating its catalytic efficiency and resistance to poisoning during ethanol oxidation reactions. , The optimized morphology typically contains numerous nanopores and a large specific surface area. Such enhancement can substantially augment ion transport within the nanostructures, thereby offering an abundance of active sites on lattice planes for the catalysis of ethanol oxidation. , Furthermore, the optimized electronic structure enhances KOH/C 2 H 5 OH adsorption and electron transfer during the reaction process, resulting in an improved recovery rate.…”
Section: Introductionmentioning
confidence: 99%